KAJIAN RAGAM PENYULUH INFORMATIF DALAM MENCEGAH ISU NEGATIF BIDANG AGAMA HINDU - Suhardi, Untung (Dharma Duta, 2019)
Abstrak The research aims to explain the tasks and functions of the in-depth informative extension that provides the construction of Hindu people in South Sumatra, knowing how to provide information on the Infomative counseling program in solving problems that often And the success of the informative counseling program in South Sumatra. This type of research uses a descriptive method of qualitative analysis. Data collection techniques are conducted by interview, observation, and collection of skunder data, while the technical data analysis is done by reducing the data display (data presentation), verfication and withdrawal of conclusions. In this study, the authors interviewed 10 informant, 6 non-civil servants, and 4 Hindus in South Sumatra. The results showed that from the informative counselling program, the spiritual Guidance program, the economic program of the general, the National educational Mental program can ward off negative issues that often occur in South Sumatra. There are factors Supporting the implementation of informative outreach program is the support of non-civil servants as well as all the concentrations of Hindus in South Sumatra so that the success of informative extension program runs optimally and is quite good. Oleh: Untung Suhardi Ketut Deni Wiryanthari Yan Mitha Djaksana I Made Biasa I Made Jaya Negara Suarsa Putra Jurusan Penerangan Agama Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta Email: untungsuhardi18@gmail.com